Budgets, Participation, and the reorganization political space - Diez Hurtado, Alejandro (2009)
This  article  tackles  the  processes  that  characterized  the  development  of  municipal  budgets in ten provinces of Cusco and Puno. The analysis focuses on the bureaucratic and political tension between the central (the State), and the peripheries (local spaces). The article analyses the participation and political positioning of diverse actors and shows that the continuation of such processes generates new forms of political articulation and reordering of local political territory. This, in turn, opens new spaces for the representation of citizenship as a dimension that is independent of electoral politics.